2003
DOI: 10.12968/bjon.2003.12.6.11241
|View full text |Cite
|
Sign up to set email alerts
|

Role of dangling when moving from supine to standing position

Abstract: This article focuses on the cardiovascular adjustments that take place when an individual makes a change in his/her position, particularly when moving from the supine to the standing position (orthostasis). Some individuals may experience a drop in their blood pressure on assuming the standing position, which may lead to dizziness and/or fainting (orthostatic intolerance). Dangling, which is often an intermediary stage of assisting people into the sitting position with their legs hanging over the side of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…[39][40][44][45][46][47][48][49][50][51][52][53][54][55][56] The final body of evidence is the most recent and includes studies conducted on early mobility in critically ill patients that provided data on feasibility, safety, and care processes. The evidence comes from 3 specific areas.…”
Section: Understanding the Physiologic Response To Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][44][45][46][47][48][49][50][51][52][53][54][55][56] The final body of evidence is the most recent and includes studies conducted on early mobility in critically ill patients that provided data on feasibility, safety, and care processes. The evidence comes from 3 specific areas.…”
Section: Understanding the Physiologic Response To Movementmentioning
confidence: 99%
“…SvO 2 is an indirect reflection of the relationship between oxygen supply and demand. [49][50][51] The most recent study by Price 50 examined the impact of sitting on the side of the bed on heart rate, blood pressure, SvO 2 , and oxygen saturation in 55 male patients after coronary artery bypass graft. In some studies, the reduction was as high as 22% in patients with low cardiac reserve.…”
Section: Response and Recovery From A Lateral Turn Or Dangling In Crimentioning
confidence: 99%
“…20, 26 Similar results have been demonstrated when initiating the dangling posture in critically ill patients. [31][32][33] In the most recent study, Price 32 examined the impact of sitting on the side of the bed on heart rate, blood pressure, SvO 2 , and oxygen saturation in 55 men who had undergone coronary artery bypass surgery. The results showed that most patients experienced an increase in heart rate, decreased blood pressure, and a reduction in SvO 2 that returned to baseline levels (for supine position) within 10 minutes.…”
Section: Response and Recovery From A Lateral Turn Or Dangling Legs Omentioning
confidence: 99%
“…21,22,[26][27][28][29][30][31][32] The third body of evidence is the most recent and includes studies of early mobility in critically ill patients that included data on feasibility, safety, and processes of care. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] responsiveness, contributing to postural hypotension and tachycardia as a result of reductions in stroke volume and cardiac output. 8,9 Head motion alone can reduce cardiac reflex response to central stimulation of the carotid baroreceptors by 30%.…”
mentioning
confidence: 99%
“…Supine to standing blood pressure-measurements provoke a greater reduction in blood pressure and increase the prevalence of OH when compared with seated to standing posture changes. 21 Studies differed in the segment of the population like age range or institutions also show fluctuated result of OH prevalence.…”
Section: The Overall Prevalence Of Ohmentioning
confidence: 99%